(untitled) (Global Journal of Human-Social Science, 2022)
One of the importance of literature is that it serves as an avenue for the study of human predicaments and solutions. Human life itself is a series of endless crises from birth to death. Therefore, based on a Freudian psychoanalytical approach to Elif Shafak’s The Forty Rules of Love and Three Daughters of Eve and by exploring some of the psychological musings of the main characters in ways that portray emotional crises among other things, this paper attempts to highlight the ambivalence attached to their seemingly prime personality. The paper is tailored around the nuances of the characters’ minds and the way they negotiate their present realities with their emotional quests and tribulations where they unconsciously apply certain defence mechanisms in their daily lives to protect their ego by creating a balance between their id and their superego. It explores the manifestation of the unconscious through sublimation, memory and nostalgia.